Oxidative stress and endothelial dysfunction - Muller, G.; Goettsch, C.; Morawietz, H. (Hämostaseologie, 2007)
This review focuses on the role of vascular oxidative stress in the development and progression of endothelial dysfunction. We discuss different sources of oxidative stress in the vessel wall, oxidative stress and coagulation, the role of oxidative stress and vascular function in arteries and veins, the flow-dependent regulation of reactive oxygen species, the putative impact of oxidative stress on atherosclerosis, the interaction of angiotensin II, oxidative stress and endothelial dysfunction, and clinical implications.
Keywords: Endothelial dysfunction; lipoproteins; nitric oxide; oxidative stress